Establishing and restructuring of the criminal investigative authority of the Republic of Belarus - Nоskevich, Ivan (Journal of the Belarusian State University. Law, 2019)
The article deals with the history of developing of criminal investigative authorities in the years since Grand Duchy of Lithuania. The article covers genesis of investigative authority, its restructuring during the time of Russian Empire and Soviet Union as well as changes in the structure of investigative authority of modern Belarus, first and foremost establishing of the Investigative Committee according to the President of the Republic of Belarus decree No. 409 dated 12th, 2011. The authour comes to the conclusion of evolusionizm of investigative authority development determined by political, social and economic trasformations.
Keywords: сriminal investigation; investigator; convention; internal affairs authority; prosecutors office; history of criminal procedure; the Investigative Committee